Evaluasi Pelaksanaan Kurikulum Tingkat Satuan Pendidikan (KTSP) Sekolah Menengah Pertama (Smp-Mts) di Kota Pekalongan Tahun 2011 - Gunawan, Muhammad Ali; Sidqi, Fajru; Haryanto, Haryanto; Wibowo, Dwi Eddy (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
This studyaims to determineanddescribeand evaluate:1)Implementation ofthe School Based Curriculum (SBC) in Junior High School in Pekalonganfromthe context, input,process,andproduct;2)the obstacles facedby schools inimplementation of School Based Curriculum (SBC) in junior High School inPekalongan.From 35Junior high schools in Pekalongan, 10 (ten)schools was taken as the samplein this study using multistagesampling technique.Data analysistechniquesused weredescriptive statisticsforthe primary data(quantitative)andqualitative for secondary data.This studyshowsthat:1)viewed from8national education standards, the implementation of School Based Curriculum (SBC)in Junior High School inPekalongan fall into thecategory of"good",with a meanscore 1.070;2)the impact ofSBConthe Education Quality of junior high school inPekalonganfrom the National ExaminationandFinal Examinationschoolscan not beconcludedbecause most schools stilladopt thecurriculumissued byBSNP;3)Constraints faced by schools inimplementing thecurriculumin junior high school in Pekalonganare:(1)the schoolshave not beenable to performcontextanalysis,analysisofopportunitiesand challenges optimally,(2)the schoolautonomyis low,(3)the schools have not beenable toconductself-evaluationbased on thecondition of the existing schools,(4)the meansand infrastructure to supportthe implementation of thecurriculumare still inadequate, especiallyin private schools,(5)manyteachers arestillteaching insome schoolsso that they can notfocuson school development,(6)the ability of teachersin preparinganddevelopingassessment instruments are low. Keywords:School Based Curriculum(SBC),Junior high school in Pekalongan